Structure of Organization and Legitimation: A Weberian Analysis of the Nizari Ismailis in Alamut (1090-1124 CE) - Fani Nur Dwi Saputro; Asep Daud Kosasih (Universitas Islam Negeri Sumatera Utara, 2026)
This study analyzes the Nizari Ismaili autonomous fortress-state at Alamut (1090-1124 CE) using Max Weber's framework to challenge the dominance of Orientalist narratives that reduce the community to Assassins while neglecting its internal structures of authority. It focuses on the organizational structure and leadership legitimation established by Hasan-i Ṣabbaḥ amid pressures from the Seljuk and Abbasid dynasties. Using a qualitative-historical literature study, sources are analyzed through Weber's Ideal Types of Authority. The findings show that the continuity of the Nizari state was sustained through the successful process of routinizing charismatic authority into an institutionalized organizational structure, manifested in a hierarchical Daʿwa system and an integrated network of defensive fortresses, which replaced unstable forms of personal loyalty. In conclusion, the Routinization of Charisma functioned as a key mechanism ensuring the stability and effectiveness of the Nizari Ismaili state while offering a sociological reinterpretation that transcends the reductive Assassin stereotype.